Relanzamiento de la marca “Dessert” - Ledesma Guzmán, Kiara Andrea (2020)
This work consists of the proposal for the relaunch of the brand Dessert that includes the development of a new identity and a digital communication campaign based on the analysis of the target audience and their digital behavior and purchase decisions. The proposal of the inbound marketing strategy in social networks, content and communication campaign was based on the analysis of the brand, the consumer and the competition, as well as research by various authors, interviews with professionals and our experience in the field of marketing. Based on this research, we developed a new logo, an identity manual containing relevant information for potential investors and a communication campaign on the Instagram social network. A website was developed to deliver valuable content and give visibility to the brand as well as a sales platform. In addition, content production was carried out that included a photo shoot reflecting the proposed new brand identity. Validations were carried out at the client, expert and potential consumer levels to optimize the visual pieces, actions and graphic factors. Finally, the results are presented through qualitative research, with the technique of focus groups on the target audience, as well as through in-depth interviews with experts.